Analysis of the propagation properties of photonic crystals with defect by the precise integration time domain method. Issue 16 (2nd November 2019) - Yang, Hongwei; Wang, Yuqi; Peng, Shuo
ABSTRACT: Propagation properties of photonic crystals with defect are analyzed by the precise integration time domain (PITD) method in the paper. The precise integration is applied to the finite difference time domain in this method. The Yee cell differential discretization technique is used in space, and the precise integration method is adopted in time. The correctness of the method is demonstrated by calculating the one-dimensional photonic crystals with defect. The transmission coefficients of the transverse electric (TE) and transverse magnetic (TM) modes in the two-dimensional photonic crystals with defect are also obtained by the method. Furthermore, the stability, precision and efficiency of the method are discussed. Numerical results reveal that the PITD method is not limited by the Courant stability condition and has higher calculation precision and efficiency, which provides a new and effective analytical method for studying the propagation properties of photonic crystals with defect.